2011
DOI: 10.1007/s00467-011-1808-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Huang Qi Huai granules on adriamycin nephrosis in rats

Abstract: Huang Qi Huai (HQH) granules, a mixture of Chinese herbs, contains trametes robiniophila murr, wolfberry fruit, and Polygonatum. We investigated the mechanism of the protective effects of HQH on adriamycin nephrosis (ADR) in rats. Adriamycin nephrotic rats were induced by a single dose of 5 mg/kg adriamycin. For the HQH-treated adriamycin nephrosis group, 1 day after treatment with 5 mg/kg adriamycin, the rats were administered once-daily oral gavage of 2 mg/kg HQH for 15 days. All the rats were killed at day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…In DXR control group, the podocyte slit pore diameters were decreased by 55.5% and up to half of the slits were tight. Thus, the filtration surface area between podocytes was Protection of rats by direct renin inhibition significantly reduced followed by broadening of the base of podocytes and disruption of the filtration slit structure, which is consistent with the previous studies [63,64]. Loss of glomerular filtration integrity was prevented in ALK 100-pretreated group, indicating that ALK has potential to prevent the DXR-induced renal damage.…”
Section: Discussionsupporting
confidence: 90%
“…In DXR control group, the podocyte slit pore diameters were decreased by 55.5% and up to half of the slits were tight. Thus, the filtration surface area between podocytes was Protection of rats by direct renin inhibition significantly reduced followed by broadening of the base of podocytes and disruption of the filtration slit structure, which is consistent with the previous studies [63,64]. Loss of glomerular filtration integrity was prevented in ALK 100-pretreated group, indicating that ALK has potential to prevent the DXR-induced renal damage.…”
Section: Discussionsupporting
confidence: 90%
“…Huai Qi Huang (HQH), a compound Chinese herbal medicine that contains Huaier, wolfberry fruit, and Polygonatum, can ameliorate proteinuria and hematuria in cases of mild IgA nephropathy [34]. HQH significantly reduces proteinuria and ameliorates tubulointerstitial damage in adriamycin nephrosis in rats [35]. The main ingredient of Huaiqihuang is Huaier, and no studies have thus far assessed the effect of Huaier in MsPGN.…”
Section: Discussionmentioning
confidence: 99%
“…Huaier cream, a Chinese traditional medicine, is a kind of Trametes robiniophila Murr., of which the extract has potent free radical-scavenging and immunomodulating properties [ 9 ]. We previously reported that Huaier exerts a protective effect in the adriamycin (ADR) nephropathy rat model by inhibiting inflammatory cytokine expression and preventing podocyte injury [ 10 ]. The proteinuria of ADR-induced rats was significantly decreased with Huaier treatments and fusion of podocyte processes was alleviated [ 10 ].…”
Section: Introductionmentioning
confidence: 99%